Growth Hormone Receptor Inhibition Sensitizes Human Pancreatic Cancer to Chemotherapy Treatments - Basu, Reetobrata (J Endocr Soc, 2021)
Human growth hormone (GH) and its cognate growth hormone receptor (GHR) have been established to have a distinct role in promoting the progression of several types of human cancers. We had earlier described a newfound role of the GH-GHR axis in driving chemoresistance in melanoma by upregulating drug efflux by ABC multidrug transporter expression and a phenotype switch by induction of epithelial-to-mesenchymal transition (EMT). Here we present an in-depth analysis of this role of GH-GHR in the highly therapy resistant human pancreatic cancer which has a 5-year survival rate of only 10% in 2020. Using human and mouse pancreatic cancer cells and RNA and protein expression analyses by RT-qPCR, ELISA, and western-blot, we identified that (i) GH upregulates specific ABC-transporter expressions in a drug-context specific manner, (ii) GH upregulates EMT transcription factors, (iii) GH activates specific oncogenic signaling pathways, and (iii) GH action increases cytochrome P450 members involved in hepatic drug metabolism. The GH antagonist, Pegvisomant, significantly inhibited these effects. Additionally, we confirmed the effects of these molecular changes by specific assays. For example, GH increases basement membrane invasion, viability of circulating tumor cells, and drug efflux; while inhibition of GHR by pegvisomant in pancreatic cancer cells reversed this aggressive tumor phenotype and sensitized the tumor cells to chemotherapy. Cell viability assays confirmed a decreased IC50 of gemcitabine, doxorubicin, and erlotinib in pancreatic cancer cells treated with pegvisomant and an increase in IC50 cells treated with GH. We further verified our results using in silico analyses of TCGA datasets for pancreatic cancer - which provided robust confirmation of our experimental findings. Presently we are validating our observation in nude mice with human pancreatic cancer cell xenografts. In conclusion, our in vitro results confirm that GHR antagonism can drastically sensitize human pancreatic cancer cells by blocking mechanisms of drug resistance, thus providing a valuable window for improved efficacy of available chemo- and targeted therapy.